Phase 1b dose-escalation, safety, and pharmacokinetic study of IC14, a monoclonal antibody against CD14, for the treatment of amyotrophic lateral sclerosis. Issue 42 (22nd October 2021) - Henderson, Robert D.; Agosti, Jan M.; McCombe, Pamela A.; Thorpe, Kathryn; Heggie, Susan; Heshmat, Saman; Appleby, Mark W.; Ziegelaar, Brian W.; Crowe, David T.; Redlich, Garry L.
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The primary objective was to demonstrate the safety and tolerability of monoclonal antibody against CD14 (IC14) (atibuclimab) in amyotrophic lateral sclerosis patients. The secondary objectives were pharmacokinetics, pharmacodynamics, and preliminary effects on disease status and biomarkers. Methods: In this open-label, dose-escalation trial, IC14 was administered at 2 mg/kg intravenous (IV) followed by 1 mg/kg/d IV × 3 (n = 3) and in subsequent patients at 4 mg/kg IV followed by 2 mg/kg/d IV × 3 (n = 7) (NCT03487263). Disease status was measured using the Revised Amyotrophic Lateral Sclerosis Functional Rating Scale, forced vital capacity, sniff nasal pressure, Edinburgh Cognitive and Behavioural ALS Screen, and Revised ALS-Specific Quality-of-Life Score. Disease biomarkers included cerebrospinal fluid and serum levels of neurofilament light chain (NfL) and urinary p75 neurotrophin receptor. Results: IC14 was safe and well tolerated. No antidrug antibodies were detected. The drug target saturation of monocyte CD14 receptors was rapid and sustained through day 8. There was no significant change in Revised Amyotrophic Lateral Sclerosis Functional Rating Scale, forced vital capacity, sniff nasal pressure, or Revised ALS-Specific Quality-of-Life Score following a single cycle of treatment. Cerebrospinal fluid NfL levels decreased in 6 of 9 patients sampled with declines of 15% to 40% between baseline (not significant [ns]) and day 8 in 3 patients. Serum NfL modestly decreased in 5 of 10 patients (ns) at day 8 and was sustained in 4 (4%-37%, ns) over 33 days of follow up. Conclusion: IC14 quickly and durably saturated its target in all patients. This study demonstrated safety and tolerability in patients with amyotrophic lateral sclerosis. Even though only a single cycle of treatment was given, there were promising beneficial trends in the neurofilament light chain, a disease biomarker. The emerging understanding of the role of systemic inflammation in neurodegenerative diseases, and the potential for IC14 to serve as a safe, potent, and broad-spectrum inhibitor of immune dysregulation merits further clinical study. Clinical Trial Registration: NCT03487263